PENGAMBILAN KEPUTUSAN DALAM PENYEDIAAN HUNIAN LAYAK HUNI BAGI MASYARAKAT BERPENGHASILAN RENDAH DI JAKARTA SELATAN - Arya Wirawan Purnomo; Raflis Raflis; Ryan Faza Prasetyo (Universitas Trisakti, 2022)
Abstract The problem that comes from year to year in Jakarta is the high demand for housing, especially for Low-Income Communities. The DKI Jakarta Government has implemented a program that is expected to be able to answer these problems by carrying out a lot of simple flats for rent or simple flats for sale construction and providing subsidies to LowIncome Communities. There are 6 Criteria and 31 Sub-Criteria that underlie the selection of a residence. Analysis of the importance level of criteria segmented according to Low-Income Communities in South Jakarta, obtained by distributing questionnaires to 100 respondents, where the 3 criteria with the highest order are safe residence, flood-free living area, availability of clean water for daily needs. The data on the importance of criteria based on Low-Income Communities are then analyzed using the Analytical Hierarchy Process by asking 5 experts for the views of what is the best alternative for providing livable housing for Low-Income Communities in South Jakarta. The selection of the location for the construction is based on 5 experts, according to expert judgment Jl. Joe belongs to a relatively quiet area that meets the criteria for a safe place to live, in the Jl. Joe also has a water channel for flood prevention in accordance with the criteria for a flood-free area, while for the availability of clean water for daily needs, the three areas in the proposed alternative have relatively the same availability of clean water.